INSTITUTION OF REFERENDUM IN POLAND – LEGAL REGULATIONS AND POLITICAL PRACTICE - Podolak, Malgorzata (Administrative and Criminal Justice, 2019)
The aim of the present paper is to analyze the legal basis of the referendum ordered by the President in Poland and demonstrate how this institution is utilized in political practice. The article assumes and proves that the fundamental condition for ordering of referendum by the President, both in legal and political terms, is the consent of the Senate. In the end this consent is determined by the distribution of political forces in the chamber. Furthermore a thesis was adopted on the political character of presidential initiatives regarding the ordering of referenda.